Pharmacokinetics and Pharmacodynamics of Ursodeoxycholic Acid in an Overweight Population With Abnormal Liver Function. Issue 1 (19th March 2020) - Yoon, Seonghae; Lee, Heechan; Ji, Sang‐Chun; Yoon, Seo Hyun; Cho, Joo‐Youn; Chung, Jae‐Yong
Abstract: Ursodeoxycholic acid (UDCA) is a secondary bile acid that is used to treat primary biliary cholangitis. Although UDCA has a hepatoprotective effect in some diseases, its benefit in nonalcoholic fatty liver disease (NAFLD) remains controversial. We aimed to evaluate the pharmacokinetics (PK) and pharmacodynamics (PD) of UDCA in overweight subjects with elevated liver enzymes after multiple administrations of UDCA and compare these changes with vitamin E treatment. Overweight subjects (body mass index, 25‐30 kg/m 2 ) with elevated alanine aminotransferase (ALT) level (40‐200 IU/L) were enrolled. Subjects received one of the following three 8‐week treatments: UDCA 300 mg twice daily UDCA 300 mg twice daily for 4 weeks followed by UDCA 300 mg twice daily and metformin 500 mg twice daily for 4 weeks, and vitamin E 400 IU twice daily. PK and PD (liver function, lipid profiles, insulin sensitivity, and miR‐122) analyses were performed. Thirty subjects were enrolled; 1 subject withdrew his consent during the study. The PK characteristics were similar to those of healthy volunteers. The ALT and miR‐122 levels decreased in the UDCA groups, whereas the ALT and aspartate aminotransferase levels decreased in the vitamin E group. The lipid profiles and insulin sensitivity did not show significant changes among the groups. There was no serious adverse event, and the safety profiles were similar among the treatment groups. The liver enzyme and miR‐122 levels were decreased by UDCA. Considering UDCA and vitamin E have a hepatoprotective effect and different mechanisms of action, combination therapy could be an option for NAFLD.